Gluteal and abdominal subcutaneous adipose tissue depots as stroma cell source: gluteal cells display increased adipogenic and osteogenic differentiation potentials. Issue 6 (June 2014) - Iwen, Karl Alexander; Priewe, Anna‐Christin; Winnefeld, Marc; Rose, Christian; Siemers, Frank; Rohwedel, Jürgen; Cakiroglu, Figen; Lehnert, Hendrik; Schepky, Andreas; Klein, Johannes; Kramer, Jan
Abstract Human adipose‐derived stroma cells (ADSCs) have successfully been employed in explorative therapeutic studies. Current evidence suggests that ADSCs are unevenly distributed in subcutaneous adipose tissue; therefore, the anatomical origin of ADSCs may influence clinical outcomes. This study was designed to investigate proliferation and differentiation capacities of ADSCs from the gluteal and abdominal depot of 8 females. All had normal BMI (22.01 ± 0.39 kg/m2) and waist circumference (81.13 ± 2.33 cm). Examination by physicians and analysis of 31 laboratory parameters did not reveal possibly confounding medical disorders. Gluteal and abdominal adipose tissue was sampled by en bloc resection on day 7 (±1) after the last menses. Histological examination did not reveal significant depot‐specific differences. As assessed by BrdU assay, proliferation of cells from both depots was similar after 24 h and analysis of 15 cell surface markers by flow cytometry identified the isolated cells as ADSCs, again without depot‐specific differences. ADSCs from both depots differentiated poorly to chondroblasts. Gluteal ADSCs displayed significantly higher adipogenic differentiation potential than abdominal cells. Osteogenic differentiation was most pronounced in gluteal cells, whereas differentiation of abdominal ADSCs was severely impaired. Our data demonstrate a depot‐specific difference in ADSC differentiation potential with abdominal cells failing to meet the criteria of multipotent ADSCs. This finding should be taken into account in future explorations of ADSC‐derived therapeutic strategies.